APLICAÇÃO FOLIAR DE FUNGICIDA NAS CARACTERÍSTICAS BROMATOLÓGICAS DA FORRAGEM E SILAGEM DE HÍBRIDOS DE MILHO - Sradler, Alan Junior (2016)
The objective of this work was to evaluate the agronomic and bromatological characteristics of forage and silage of corn hybrids with different grain textures submitted to chemical application of fungicide in two seeding seasons. The experimental design was randomized blocks in a 4 x 2 factorial scheme, four corn hybrids, without and with fungicide, in two seeding seasons, with four replications. The hybrids used were: DKB 240 PRO, AS 1572 PRO, P32R48YH and AG 8690 PRO3. The seeding times adopted were: October and December. The treatments were: the first with two applications (Trifloxystrobin + Prothioconazole) in V8 and R1, and the second without application of fungicide. The following characteristics were evaluated: forage green matter yield (FGMY), forage dry matter percentage (FDM%), forage dry matter yield (FDMY), silage dry matter percentage (SDM%), silage dry matter yield (SDMY), grain yield (GY), vitreousness (VIT), forage neutral detergent fiber (FNDF), and silage (SNDF), forage acid detergent fiber (FADF) and silage (SADF), forage in situ digestibility (FDIG) and silage (SDIG), the area under the progress curve of common rust (AUPCR) and leaf spot of diplodia (AUPCD). The results were submitted to analysis of variance, the means compared to each other by the Tukey test at 5% probability and three orthogonal contrasts were performed. The seeding season in the month of October positively influenced the characteristics of forage and silage in forage hybrids. The hybrids DKB 240 PRO, AS 1572 PRO and AG 8690 PRO3 obtained the best productivity of green mass, dry mass and grains, when the seeding season was used in the month of October. The application of fungicide reduced the levels of neutral detergent fiber (NDF) and acid detergent fiber (FAD) obtained at the forage point and and the silage. The seeding season in December negatively influenced the bromatological parameters. The application of fungicide in V8 and R1 positively influenced in situ digestibility at the forage point and in the silage produced, regardless of the seeding season. The application of fungicide in V8 and R1 reduces the severity of common rust and leaf spot of diplodia in forage corn hybrids, depending on the seeding season. Seeding in December reduced the yield of green matter and grain yield due to the increase in the severity of common rust and leaf spot of diplodia in the evaluated forage hybrids. The DKB 240 PRO and AG 8690 PRO3 hybrids obtained the highest yields of green matter and the AG 8690 PRO3 hybrid obtained the highest grain yield, regardless of the seeding season.